PERFORMANCE ENHANCEMENT THROUGH SKILL DEVELOPMENT INITIATIVES AMONG WOMEN ENTREPRENEURS IN CUDDALORE DISTRICT - UMAMAHESWARI , M. (International Journal of Psychosocial Rehabilitation, 2020)
Skill is the ability or the capacity acquired through constant deliberate, systematic and sustained effort to execute complex activities, job, things or lives. Skill is the summation of several types of competencies which encapsulate many abilities, commitments, knowledge and skills. Descriptive research design and structure questionnaire are adopted. Sample size of the research is 75 women entrepreneurs selected through simple random sampling technique. The analysis discovered that there is influence of factors of skill development initiatives such as management skills, leadership skills and technical skills on entrepreneurial creativity. The analysis also identified that there is influence of management skills and technical skills on performance of women entrepreneurs. It is found that there is influence of entrepreneurial creativity on performance of women entrepreneurs. Hence, it is concluded that activities like exhibition of advanced production technologies, seminars on different managerial strategies required and other kind of intervention activities are in dire need to enrich the performance of business clusters as well as to women entrepreneurs.